Evaluation of the Performance of Bushehr's Medical Sciences University and Health Service Center Based on the Organizational Excellence Model of Europe's Quality Management Foundation - Rastgoo, Parvaneh (International Review of Management and Marketing, 2017)
The present study was aimed to evaluate performance in Bushehr's Medical Sciences University and Health Service Center based on the organizational excellence model of Europe's Quality Management Foundation. The present research was practical in terms of objective; and in terms of data collection method, it was descriptive-survey. The statistical population consisted of 2000 students from Bushehr's Medical Sciences University and Health Service Center, from whom 322 individuals were selected as sample size, using Morgan Table and a stratified random sampling method. In order to collect data, a standard organizational excellence questionnaire (EFQM) (2010) with 55 items was used. Using Cronbach's alpha, the reliability of the questionnaire was calculated to be 0.82; in addition, in order to calculate the validity of the questionnaire, content validity was used; then the questionnaire was approved by experts. Data analysis was done using SPSS software in two sections: inferential and descriptive (single-sample "t" test). Findings showed that organizational excellence in Bushehr's Medical Sciences University and Health Service Center was in a favorable level (higher than a medium level) for components such as leadership, strategies, employees, partnership, resources, processes, employee results, society results, key results, and customer results. Keywords: customer results, organizational excellence, organizational excellence model of Europe's quality management foundation, performance evaluation JEL Classifications: C32; O13; O47